Analisis Tingkat Pelayanan Service Kendaraan dan Penjualan Produk Sepeda Motor dengan Service Quality - Agung Pratama; Rizky Fauziah; Febby Madonna Yuma (LPPM STMIK Royal Kisaran, 2021)
Abstract: Based on available data, it is known that motorcycle sales at Panca Prima Abadi Dealers fluctuate every year. This resulted in several types of motorcycles that did not reach the sales target and affected operating income. The Panca Prima Abadi dealer realized that customers would return to buy motorcycles if they received good service. There are some customers who feel that the quality of service is relatively low so that in solving problems that cannot be solved optimally. The problem of vehicle service quality is supported by evidence of the changing number of customers who have performed service for the last 3 (three) years. To overcome this problem, a decision support system is made that will make it easier for Panca Prima Abadi Dealers to find out how the quality of motorcycle service has been provided to customers so far. Based on the calculation of the analysis of the level of service vehicle service and sales of motorcycle products using the Service Quality method, it can be concluded that the vehicle service has a